Pengaruh Pengetahuan dan Kesadaran Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Tamansari Kabupaten Bogor - Muiz, Muhamad Abdul; Dali, Rahmat Mulyana; Yudiana, Yudiana (Peneliti.net, 2024)
This research is intended to determine the effect of knowledge and awareness of taxpayers on taxpayer compliance in paying Land and Building Tax (PBB) in Kecamatan Tamansari kabupaten bogor. The sample in this research is the existing taxpayer District Kecamatan Tamansari Kabupaten Bogor as many as 100 respondents. The techniquesampling in this research is using simple random sampling. The type of data used in this study is quantitative data in the form of scores or scores on answers given by respondents to the questions that exist in the questionnaire. Sources of data used are primary data and secondary data. Primary data obtained from direct observation, interview, questionnaire and observation while secondary data obtained by researcher in the form of data report of result of tax payment from research object. Methods of data analysis using data quality test, classical assumption test, multiple regression analysis and hypothesis test. Based on the results of research that has been done can be concluded that there is a significant positive influence between taxpayer knowledge and taxpayer awareness of taxpayer compliance in paying taxes of the earth and buildings on Kecamatan Tamansari Kabupaten Bogor.